Pediatric infective endocarditis initially presenting as hemorrhagic stroke - Emir Yonas; Raymond Pranata; Vito Damay; Nuvi Nusarintowati (Paediatrica Indonesiana, 2020)
Infective endocarditis refers to infection of the heart valves. While its incidence is low, it may cause serious complications. Despite advances in its management and diagnosis, this condition still retains high mortality and significant morbidity. Considerable controversy remains regarding antimicrobial prophylaxis to prevent infective endocarditis in patients with congenital heart disease. Neurologic complications are the second most common complication in patients with infective endocarditis, occurring in approximately 33% of cases.1 These include encephalopathy, meningitis, stroke, brain abscess, cerebral hemorrhage, and seizures. The vegetation formed as a consequence of endocarditis may dislodge and cause embolization. Vegetation size alone is an unreliable marker for embolization risk, however, size, in addition to location, mobility, infecting agent, and presence of antiphospholipid antibodies have the potential to be prognostic markers. The brain is the most frequent site of embolization. Furthermore, advances in medical approaches have resulted in an increase of patients at risk of endocarditis due to the now common and widely available indwelling intravascular approaches in medicine. In this report, we present a case of infective endocarditis in a child first presenting with hemorrhagic stroke.1,2